297. ESOPHAGECTOMY IN ELDERLY PATIENTS WITH ESOPHAGEAL CANCER: A FIVE-YEAR EXPERIENCE FROM A CANCER CENTRE IN NORTH-EAST INDIA. (24th September 2022) - Das, Gaurav; Talukdar, Abhijit
Abstract: North-East India has a high incidence of esophageal cancer. An elderly patient with esophageal cancer often has multiple comorbidities and compromised general condition and so, esophagectomy in this population is associated with more morbidity and mortality. Our objectives were to estimate the 30-day morbidity and mortality and estimate the disease-free and overall survival and recurrence patterns. Retrospective, observational single institute study. We included all patients with age ≥ 60 years with a proven diagnosis of esophageal cancer and who underwent an esophagectomy during the study period from 1st January 2016 to 31st December 2020. Data was collected from patient's records and the results were presented using median values, range and percentages. There were 35 patients; median age was 65 years (range 60 to 76 years). Neoadjuvant chemotherapy (40.0%) was used more than chemoradiation (31.4%). Procedures included trans-thoracic esophagectomy (68.6%), trans-hiatal esophagectomy (25.7%) and left thoraco-abdominal approach (5.7%). 30-day mortality rate was 8.6% (aMI, COVID pneumonia and ARDS). 30-day morbidity rate was 40%, with pulmonary (25.7%), hoarseness of voice (17.1%), anastomotic leak (14.3%), wound infection (11.4%), symptomatic cardiac arrhythmias (5.7%) and septicaemia (2.9%) being part of the spectrum. 8.5% had locoregional recurrence and 5.7% had distant recurrence (peritoneum, bones and liver). Median overall survival was 33 months (range 9 to 43 months). Esophagectomy in elderly patients carry a high risk of 30-day morbidity and mortality, but has acceptable overall survival.